Hydrostatic and hybrid bearing design - Rowe, W. B. (William Brian) (Butterworths, 1983)
Hydrostatic and Hybrid Bearing Design is a 15-chapter book that focuses on the bearing design and testing. This book first describes the application of hydrostatic bearings, as well as the device pressure, flow, force, power, and temperature. Subsequent chapters discuss the load and flow rate of thrust pads; circuit design, flow control, load, and stiffness; and the basis of the design procedures and selection of tolerances. The specific types of bearings, their design, dynamics, and experimental methods and testing are also shown. This book will be very valuable to students of engineering des.